Data from: Extensive heterosis in growth of yeast hybrids is explained by a combination of genetic models - Shapira, Rachel; Levy, Tal; Shaked, Silvia; Fridman, Eyal; David, Lior (Dryad, 2014)
Heterosis, also known as hybrid vigor, is the superior performance of a
heterozygous hybrid relative to its homozygous parents. Despite the
scientific curiosity of this phenotypic phenomenon and its significance
for food production in agriculture, its genetic basis is insufficiently
understood. Studying heterosis in yeast can potentially yield insights
into its genetic basis, can allow one to test the different hypotheses
that have been proposed to explain the phenomenon and allows better
understanding of how to take advantage of this phenomenon to enhance food
production. We therefore crossed 16 parental yeast strains to form 120
yeast hybrids, and measured their growth rates under five environmental
conditions. A considerable amount of dominant genetic variation was found
in growth performance, and heterosis was measured in 35% of the
hybrid–condition combinations. Despite previous reports of correlations
between heterosis and measures of sequence divergence between parents, we
detected no such relationship. We used several analyses to examine which
genetic model might explain heterosis. We found that dominance
complementation of recessive alleles, overdominant interactions within
loci and epistatic interactions among loci each contribute to heterosis.
We concluded that in yeast heterosis is a complex phenotype created by the
combined contribution of different genetic interactions.
Table S3. Strain growth phenotypes under five conditions.This table
contains the doubling time value of all strains under five conditions. For
each strain, replicate measurements are included.Table S3.xlsxTable S4.
Growth phenotype of the 7 x 37 BC1 population.This file contains the mean
doubling time of parents, hybrid and each BC1 strain under two
temperatures.Table S4.xlsxTable S5. Growth phenotype of the 38 x 37 BC1
population.This file contains the mean doubling time of parents, hybrid
and BC1 strains under two temperatures.Table S5.xlsx
Keywords: Hybrid vigor; Complex trait; Epistasis; present; Dominance complementation; Overdominance